The D-Test: a new tool for assessing the agility of young soccer players in pre-formation categories - Segui, R.; Dellal, A.; Pialoux, V.; Hautier, C. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: The development of the agility is essential in young soccer players, and it constitutes the aim of the training in the process of pre-formation. However, the majority of agility test is destined for the talent identification or adult players. Therefore, it appears that there is a lack of specific tool to test the agility and motricity especially in pre-formation categories. Consequently, the aim of this study was to examine the interest of a new tool, the D-Test, and to show if this test discriminate the agility skills in soccer either by category or the playing positions in youth players of pre-formation. Methods: 60 young elite players from the pre-formation categories of the same club (Olympique Lyonnais FC) participated in this study: U13(n=19, height: 151.4±7.8 cm, body mass: 42.1±6.4 kg), U14 (n=21, height: 163.7±7.6 cm, body mass: 52.32±7.8 kg) and U15 (n=20, height: 167.7±8.2 cm, body mass: 54.2±9.2 kg)including in whole categories 6 goalkeepers, 7central defenders, 14full-backs, 13 axial midfielders, 13 external midfielders and 7 forwards. All players performed 3 times the D-Test (2 trials) in 3 different period of the competitive season 2011-2012. The conditions were standardized with the application of the test on a new-generation artificial turf in the same of the day and the performances were measured using photocell (Polifemo© Microgate, Bolzano- Bozen, Italy) placed at hip height. Practically, the D-Test consisted by the combination of the following sequence (on 20m): rolling start, lateral motricity (3m + 3m), ground reaction footwork with a rhythm hurdle (4x40cm), three short acceleration short (3x4m) interspaced by two180° changes of directions with an alternance of the leg used (one time with the right leg and the other time with the left leg). Results: A significant difference between age group (F= 6-60, p<0.01)was found. The U13 had significantly slower performance in the D-Test compared to U14 (p<0.01) and U15 (p<0.01). Moreover, the inter group analysis showed no significant difference between playing positions (p<0, 05), whereas a significant difference were observed in U13 and U14 with greater performance of external midfielders and forwards (p<0.05). Discussion: The major findings of the present study demonstrated that the D-Test is an interesting assessment tool in the determination of the agility skills of young soccer players according to the playing position, allowing to direct the specific method of individual training.